Clinical Outcomes Of Induction TherapyWith Addition Of High Dose Methotrexate And Cytarabine To Existing Standard Treatment In Patients With Newly Diagnosed Diffused Large B-Cell Lymphoma: A Retrospective Study - Dang, Chee Chean (2018)
Diffuse large B-cell lymphoma (DLBCL) is a heterogenous group of diseases with various outcomes depending on the clinical and biological features. Optimal induction therapy for high-risk DLBCL is still unclear, and clinical trials are needed to evaluate alternative approaches. This study aimed to evaluate the response rates and long term remission of induction therapy with addition of high dose methotrexate and cytarabine onto RCHOP for patients diagnosed with DLBCL. 62 DLBCL patients diagnosed between January 2011 to December 2014 were retrospectively analyzed.